Multivalency in the recognition and antagonism of a HIV TAR RNA–TAT assembly using an aminoglycoside benzimidazole scaffold. Issue 6 (14th January 2016) - Kumar, Sunil; Ranjan, Nihar; Kellish, Patrick; Gong, Changjun; Watkins, Derrick; Arya, Dev P.
Abstract : Recognition of RNA by high-affinity binding small molecules is crucial for expanding existing approaches in RNA recognition, and for the development of novel RNA binding drugs. Abstract : Recognition of RNA by high-affinity binding small molecules is crucial for expanding existing approaches in RNA recognition, and for the development of novel RNA binding drugs. A novel neomycin dimer benzimidazole conjugate5 (DPA 83) was synthesized by conjugating a neomycin-dimer with a benzimidazole alkyne using click chemistry to target multiple binding sites on HIV TAR RNA. Ligand5 significantly enhances the thermal stability of HIV TAR RNA and interacts stoichiometrically with HIV TAR RNA with a low nanomolar affinity.5 displayed enhanced binding compared to its individual building blocks including the neomycin dimer azide and benzimidazole alkyne. In essence, a high affinity multivalent ligand was designed and synthesized to target HIV TAR RNA.